Coordinated decentralized and centralized microgrid control for distributed renewable energy sources with integrated batteries - Issarachai Ngamroo; Tossaporn Surinkaew (My University, 2022)
Abstract Renewable energy sources (RESs) with integrated batteries (IBESSs) in microgrid (MGs) have well been developed by aggregate models in previous research works. Either decentralized or centralized control is applied as a standard platform to manage the aggregate models. However, these may not be valid assumptions in practical MGs, which consist of various distributed RESs with IBESSs and control platforms. As a result, controllers designed for the aggregate models may be ineffective, when they are applied for distributed models in actual MGs. To deal with these problems, this paper proposes a coordinated decentralized and centralized MG control strategy of distributed RESs and IBESSs (DIBESSs). New modellings of the distributed RESs with DIBESSs are developed here so that appropriate controllers can be designed to manage voltage and frequency of a MG. An adaptive‐robust approach is applied to achieve flexible control performance of the RESs with DIBESSs against MG uncertainties, operating points, and conditions. Comparative analyses of the conventional, aggregate, and distributed models are made. Simulation results in an inertia‐less microgrid with 100% RESs verify the capability of the proposed control strategy for the distributed models.
Keywords: Microgrid; Decentralised system; Microgrid Control and Optimization